Parkinson’s Disease–Mild Cognitive Impairment (PD-MCI): A Useful Summary of Update Knowledge - Cammisuli, Davide Maria; Cammisuli, Salvatore Massimiliano; Fusi, Jonathan; Franzoni, Ferdinando; Pruneti, Carlo (Frontiers in Aging Neuroscience, 2019)
Mild cognitive impairment (MCI) is a common feature in Parkinson’s disease (PD), even at the time of diagnosis. Some levels of heterogeneity in nature and severity of cognitive impairment and risk of conversion to Parkinson’s disease dementia (PDD) exists. This brief overview summarized current understanding of MCI in PD, by considering the following major points: historical development of the clinical entity, evaluation, epidemiology, predictors and outcomes, neuroimaging findings, pathophysiology, treatment, pharmacological and non-pharmacological intervention. MCI in PD represents a concept in evolution and plays a pivotal role in advancing our understanding of the disease mechanisms, with the ultimate goal of building effective strategies to prevent conversion into Parkinson’s disease dementia. Challenges for future research are also discussed.